Faktor-Faktor Yang Berpengaruh Terhadap Stunting Di Tujuh Desa PKMD Kecamatan Sungai Tebelian Kabupaten Sintang Tahun 2023 - Uray B. Asnol (Pusat Riset dan Inovasi Nasional, 2023)
Health is a primary need for every human living in the world, and health development basically involves physical and mental health. A person's health condition will affect a person's socio-economic life, as well as the sustainability of a nation's life, both in developed countries and in developing countries such as Indonesia.